Energy and exergy analysis of integrated system of ammonia–water Kalina–Rankine cycle. (October 2015) - Chen, Yaping; Guo, Zhanwei; Wu, Jiafeng; Zhang, Zhi; Hua, Junye
Abstract: The integrated system of AWKRC (ammonia–water Kalina–Rankine cycle) is a novel cycle operated on KC (Kalina cycle) for power generation in non-heating seasons and on AWRC (ammonia–water Rankine cycle) for cogeneration of power and heating water in winter. The influences of inlet temperatures of both heat resource and cooling water on system efficiencies were analyzed based on the first law and the second law of thermodynamics. The calculation is based on following conditions that the heat resource temperature keeps 300 °C, the cooling water temperature for the KC or AWRC is respectively 25 °C or 15 °C; and the temperatures of heating water and backwater are respectively 90 °C and 40 °C. The results show that the evaluation indexes of the power recovery efficiency and the exergy efficiency of KC were respectively 18.2% and 41.9%, while the composite power recovery efficiency and the composite exergy efficiency of AWRC are respectively 21.1% and 43.0% accounting both power and equivalent power of cogenerated heating capacity, including 54.5% heating recovery ratio or 12.4% heating water exergy efficiency. The inventory flow diagrams of both energy and exergy gains and losses of the components operating on KC or AWRC are also demonstrated. Highlights: An integrated system of AWKRC (ammonia–water Kalina–Rankine cycle) is investigated. NH3 –H2 O Rankine cycle is operated for cogenerating power and heating-water in winter. Heating water with 90 °C and capacity of 54% total reclaimed heat load is cogenerated. Kalina cycle is operated for power generation in other seasons with high efficiency. Energy and exergy analysis draw similar results in optimizing the system parameters.